Mosaic variants in the LIM homeobox 1 (LHX1) gene contribute to Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome - Dina Kira; Soumia Brakta; Hyung Goo Kim; Jennifer Butler; Lynn P. Chorich; John A. Phillips; Lawrence C. Layman (Human Genetics, 2026)

Viability of seed balls for large-scale restoration of native plant communities in New Zealand - James W. Griffiths; Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; Jennifer Alderton-Moss; Karin van der Walt; Anja McDonald; Kirsty Moran (New Zealand Journal of Botany, 2025)

How Do Synchrony in Survival and Productivity Influence Abundance Synchrony in European Landbirds? - Catriona A. Morrison; Jennifer A. Gill; Claire Buchan; Robert A. Robinson; Juan Arizaga; Oriol Baltà; Emanuel Baltag; Jaroslav Cepák; Pierre‐Yves Henry; Ian Henshaw; Zsolt Karcza; Petteri Lehikoinen; et al. (Ecology Letters, 2025)
Synchronous fluctuations in species' abundance are influenced by synchrony in underlying rates of productivity and survival. However, it remains unclear how rate synchrony varies in space and time, contributes to abundance synchrony, and differs among species. Using long‐term annual count (number of adults captured), adult survival and productivity (number of juveniles captured per adult) data for breeding land‐birds at ringing sites across Europe, we show that synchrony is strongest and largest scale in productivity and weakest and smallest scale in counts. However, counts fluctuate more synchronously with survival than they do with productivity. These patterns hold for species which do not migrate or only migrate within Europe (European‐residents) and those migrating to sub‐Saharan Africa (subSaharan‐migrants), but the periodicity of productivity and survival synchrony is longer in European‐residents than in subSaharan‐migrants. This suggests that survival and productivity synchrony may interact to weaken abundance fluctuations but are influenced by environmental drivers operating over differing timescales in European‐resident and subSaharan‐migrant species.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Understanding mechanisms of racial disparities in breast cancer: an assessment of screening and regular care in the Carolina Breast Cancer Study - Matthew R. Dunn; Eman M. Metwally; Sanah Vohra; Terry Hyslop; Louise M. Henderson; Katherine Reeder-Hayes; Caroline A. Thompson; Jennifer Elston Lafata; Melissa A. Troester; Eboneé N. Butler (Cancer Causes & Control, 2024)

Classifying 3-D Models of Coral Reefs Using Structure-From-Motion and Multi-View Semantic Segmentation - Jordan Pierce; Mark J. Butler; Yuri Rzhanov; Kim Lowell; Jennifer A. Dijkstra (Frontiers in Marine Science, 2021)
Benthic quadrat surveys using 2-D images are one of the most common methods of quantifying the composition of coral reef communities, but they and other methods fail to assess changes in species composition as a 3-dimensional system, arguably one of the most important attributes in foundational systems. Structure-from-motion (SfM) algorithms that utilize images collected from various viewpoints to form an accurate 3-D model have become more common among ecologists in recent years. However, there exist few efficient methods that can classify portions of the 3-D model to specific ecological functional groups. This lack of granularity makes it more difficult to identify the class category responsible for changes in the structure of coral reef communities. We present a novel method that can efficiently provide semantic labels of functional groups to 3-D reconstructed models created from commonly used SfM software (i.e., Agisoft Metashape) using fully convolutional networks (FCNs). Unlike other methods, ours involves creating dense labels for each of the images used in the 3-D reconstruction and then reusing the projection matrices created during the SfM process to project semantic labels onto either the point cloud or mesh to create fully classified versions. When quantitatively validating the classification results we found that this method is capable of accurately projecting semantic labels from image-space to model-space with scores as high as 91% pixel accuracy. Furthermore, because each image only needs to be provided with a single set of dense labels this method scales linearly making it useful for large areas or high resolution-models. Although SfM has become widely adopted by ecologists, deep learning presents a steep learning curve for many. To ensure repeatability and ease-of-use, we provide a comprehensive workflow with detailed instructions and open-sourced the programming code to assist others in replicating our methodology. Our method will allow researchers to assess precise changes in 3-D community composition of reef habitats in an entirely novel way, providing more insight into changes in ecological paradigms, such as those that occur during coral-algae shifts.

How do birds look at their world? A novel avian visual fixation strategy - Shannon R. Butler; Jennifer J. Templeton; Esteban Fernández-Juricic (Behavioral Ecology and Sociobiology, 2018)

A Novel Aza-MBP Altered Peptide Ligand for the Treatment of Experimental Autoimmune Encephalomyelitis - Nicole N. M. Trager; Jonathan T. Butler; Jennifer Harmon; Joshua Mount; Maria Podbielska; Azizul Haque; Naren L. Banik; Craig C. Beeson (Molecular Neurobiology, 2018)

Optimal visual–vestibular integration under conditions of conflicting intersensory motion profiles - John S. Butler; Jennifer L. Campos; Heinrich H. Bülthoff (Experimental Brain Research, 2015)

Contributions of visual and proprioceptive information to travelled distance estimation during changing sensory congruencies - Jennifer L. Campos; John S. Butler; Heinrich H. Bülthoff (Experimental Brain Research, 2014)

Recent environmental change and trace metal pollution in World Heritage Bathurst Harbour, southwest Tasmania, Australia - Krystyna M. Saunders; Jennifer J. Harrison; Edward C. V. Butler; Dominic A. Hodgson; Andrew McMinn (Journal of Paleolimnology, 2013)

Sex differences in neuroadaptation to alcohol and withdrawal neurotoxicity - Lynda Sharrett-Field; Tracy R. Butler; Anna R. Reynolds; Jennifer N. Berry; Mark A. Prendergast (Pflügers Archiv - European Journal of Physiology, 2013)

An In Vitro Methodology for Forecasting Luminal Concentrations and Precipitation of Highly Permeable Lipophilic Weak Bases in the Fasted Upper Small Intestine - Dimitrios Psachoulias; Maria Vertzoni; James Butler; David Busby; Moira Symillides; Jennifer Dressman; Christos Reppas (Pharmaceutical Research, 2012)

Multisensory integration in the estimation of walked distances - Jennifer L. Campos; John S. Butler; Heinrich H. Bülthoff (Experimental Brain Research, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Viable Transgenic Goats Derived from Skin Cells - Esmail Behboodi; Erdogan Memili; David T. Melican; Margaret M. Destrempes; Susan A. Overton; Jennifer L. Williams; Peter A. Flanagan; Robin E. Butler; Hetty Liem; Li How Chen; Harry M. Meade; William G. Gavin; et al. (Transgenic Research, 2004)